Islamic Finance Transformation: A Bibliometric Analysis - Ganjar Primambudi; Muhammad Ariful Maarif (Universitas Muhammadiyah Yogyakarta, 2024)
This research paper aims to comprehensively examine the evolution, themes, and trends within Islamic finance transformation. This study used bibliometric analysis in biblioshiny R-Studio to collect and analyze relevant scholarly sources. We perform citation network analysis, co-authorship analysis, and keyword co-occurrence analysis to identify the intellectual structure in Islamic finance transformation. We found that Malaysia is the most outstanding country in this topic, the Journal of Islamic Accounting and Business Research is the most outstanding journal, and International Islamic University Malaysia is the most outstanding affiliation. Our study also reveals a notable increase in publications on Islamic finance transformation over the past decade, indicating growing interest. Key themes identified include fintech, regulatory frameworks, ethics, and Islamic-conventional finance integration. We highlight influential scholars and journals shaping the field, showcasing its multidisciplinary nature. This research offers a comprehensive overview of Islamic finance transformation literature, synthesizing themes and highlighting ongoing research areas. The bibliometric analysis provides quantitative insights into influential works and scholars, serving as a valuable resource for researchers, policymakers, and practitioners navigating the evolving landscape of Islamic finance.